Accountability of Local Authorities in Accessing Land Information of Ethnic Minorities in Binh Dinh Province - Pham Thi Hang; Nguyen Thi Hai; Nguyen Van Binh; Nguyen Huu Ngu (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis)
The study was conducted to test the impact of accountability on access to land information for ethnic minorities. The research model of the article is a linear structural equation model (SEM). The partial least squares (PLS) method was used to test the SEM model with 372 survey samples of households and individuals of the Cham, Bana, and H're ethnic minorities in Binh Dinh province, Vietnam. Research results show that accountability is vital in promoting and improving the effectiveness of ethnic minorities' access to land information. Accountability is considered a mechanism to monitor managers' behavior and ensure land users' rights and interests in accessing land information. The research results confirm that a strong relationship exists between accountability and access to land information of ethnic minorities. Improve accountability of state land management agencies to help land users, predominantly ethnic minority land users, and those considered disadvantaged in society perform better and be more suitable to access land information. This relationship is shown through the research model's significance level of 1% (t value = 11.130); the coefficient β to evaluate the relationship from accountability to access to land information is 0.5. The estimated path coefficient β, close to +1, indicates a strong positive relationship. The research results provide some suggestions for continuing to promulgate regulations and policies to strengthen further the implementation of state land management agencies' accountability towards improving the effectiveness of ethnic minorities' access to land information.